Black phosphorus nanoparticles for dual therapy of non-small cell lung cancer. (3rd July 2022) - Lin, Zhongxiao; Deng, Qiudi; Fang, Qi; Li, Xinzhi; Liu, Xiaoyan; Wang, Jianglin; Chen, Sheng; Huang, Xiaotao; Yang, Langyu; Miao, Yingling; Yu, Xi-Yong
Abstract: Lung cancer remains one of the leading causes of death in humans. Gefitinib is an inhibitor of epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) commonly used to suppress tumour growth. However, constantly use of gefitinib results in drug-resistance, reduced efficacy and undesired side effects. To circumvent these drawbacks, targeted and photothermal therapies have emerged as effective strategies. Herein, we are first to adopt a black phosphorus (BP) nanoparticle-based novel delivering strategy by combining gefitinib and cancer cytomembrane to treat non-small cell lung cancer (NSCLC). In these gefitinib-containing nano-carriers, cyanine 5 (Cy5) biotin-labelled BP was incorporated with cancer membrane and then consists of a nanomaterial (BPGM), which enabled to deliver gefitinib to the tumours effectively. The combination of BPGM showed reinforcing effects to suppress NSCLC cells and xenograft tumours without apparent adverse effects both in vitro and in vivo . BPGM facilitated the delivery of gefitinib to tumour tissue and extended its retention time within tumours. These studies thus suggest that BP may serve as novel delivery strategy for lung cancer.